Analisis Hukum Isbat Nikah dalam Perkawinan di Bawah Umur Tidak Tercatat Menurut Undang-Undang No. 16 Tahun 2019 - Ramadi, Bagus; Yuslem, Nawir; Hamdani, Faisal (ARBITER: Jurnal Ilmiah Magister Hukum, 2023)
This research explores the challenges faced by society following the increase in the legal age of marriage from 16 to 19 years. Certain groups, particularly those adhering to the tradition of early marriages, encounter obstacles. Due to the perceived difficulties in obtaining marriage dispensations, some individuals opt for underage marriages without formal registration, relying on the subsequent process of marriage confirmation (isbat nikah). This qualitative study employs a juridical-normative method with a statue approach, analyzing the Marriage Law and Compilation of Islamic Law (KHI) concerning marriage confirmation in underage unions. The findings indicate that while the Marriage Law does not specifically regulate marriage confirmation, the provisions are found in the KHI. Marriage confirmation can be sought based on the absence of marriage impediments according to Law No. 1 of 1974, including marriages conducted below the stipulated age. Thus, from a juridical perspective, individuals marrying underage may potentially file for marriage confirmation in the Religious Court if there are no impediments, as specified in the KHI.